Breeding Behaviour, Sex Ratio, and Sexual Dimorphism in the Frog, Rana Curtpes: Geographical Variation in Breeding Behavior and Morphology of Rana Curtpes (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Several local populations of the moor frog (Rana arvalis) from the southern part of the range (the Ukraine) were compared by size and age composition and morphological characters in males and females with one of the populations from Moscow Region (Zvenigorod Biological Station-ZBS). In spite of close geographical location of the Ukrainian populations (not more than 40 km), they differ significantly both in mean body size and age. At that, mean value of these parameters turned out to be lower than the corresponding values for the ZBS population. In southern populations, the proportion of females breeding for the first time right after the second hibernation is higher than males comparing to the ZBS population, the part of two-years-old mature specimens of both sexes is higher while the part of older specimens is lower. This geographical variability of age composition causes significantly lower mean age and body size of specimens from the southern populations. Although in the Ukraine the activity season is longer than in Moscow Region, the growth rate of two- and three-year-old frogs from southern populations is lower, and only at age of four they become larger than specimens from the ZBS population. These differences are caused by higher reproductive effort both in females and males from southern populations.